Love and anger in Amazonia and in academia: a disciple’s account of Joanna Overing’s oeuvre and teachings - Carlos D. Londoño Sulkin (Journal de la Société des Américanistes)
In the Caquetá, Colombia, in 1995, I asked an Englishman who was doing fieldwork for his Ph.D. at Oxford for advice about graduate studies in the UK. “Maybe consider going to Joanna Overing,” he recommended. He thought that she and her students were doing the most exciting research in Amazonianist anthropology at the time. Meeting him was the first in a chain of fortunate events that led to my doing a Ph.D. under Joanna’s supervision and witnessing a golden but embattled era in her career. This is my personal account of her loves and peeves, her generous supervisory style, her theories, and her place in the history of our discipline and regional specialization, as I now see these. Regarding the latter, I focus especially on her brilliant writing on how contingent associations of Western anthropologists’ analytical terms hinder proper understanding of others’ political philosophies and ways of life; I attend as well to her attention to the centrality of moral understandings in social life, and to her participation in debates about Amazonian engagements with alterity, consanguinity, and conviviality.